Bicycles gathering dust rather than raising dust – Prevalence and predictors of cycling among Australian schoolchildren. Issue 5 (September 2015) - Carver, Alison; Timperio, Anna F.; Crawford, David A.
Abstract Objectives To examine social and physical environmental correlates of cycling regularly (i.e. at least once per week) among school-aged children. Design Cross-sectional study of 430 primary (48% boys; 72% urban) and 258 secondary school-aged children (52% boys; 51.6% urban) in Victoria, Australia. Methods Children survey-reported their frequency of cycling during a typical week. Parents survey-reported on traffic concern, social trust and whether their child was allowed to cycle alone on main roads. Using a Geographic Information System each child's home was mapped along with bike paths, sports/recreational facilities and shops within 800 m and 5000 m (using pedestrian/cyclist network buffers). Logistic regression analyses examined associations between these explanatory variables and the odds of cycling at least once per week. Results Factors associated with reduced odds of cycling at least once per week were: being a girl rather than a boy (odds ratio = 0.53, 95% confidence interval 0.38–0.74); and the number of types of sports facilities located with 5000 m of home (odds ratio = 0.87; 95% confidence interval 0.78–0.97). Factors associated with increased odds of this were: bike path provision (top tertile) within 5000 m of home (odds ratio = 1.70; 95% confidence interval 1.11–2.61) and being allowed to cycle alone on main roads (odds ratio = 1.75, 95% confidence interval 1.22–2.52). Conclusions Further research is required to inform interventions to promote children's cycling, e.g. by skill-building so that parents feel comfortable allowing their child to cycle without adult accompaniment. Natural experiments are also needed to evaluate the impact of new cycling infrastructure on rates of cycling among children and the broader population.